PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN IPS - Hakim, Zerri Rahman; Riyani, Estu (ATTA`DIB, 2015)
The purpose of this study is to improve the learning activities and learning outcomes of students in sixth grade elementary school (SD) of Singapadu especially in social studies (IPS) using Problem Based Learning model application. Based on the results of the study, the researchers can sum up that using Problem Based Learning model can improve student learning activities in social studies (IPS) learning. This can be seen from the first cycle studies reached 70%, and the second cycle students’ activity reached 90%. The use of Problem Based Learning model can improve student learning outcomes in social studies (IPS) learning. This can be seen from the results of the first cycle studies reached 69% or 16 students who passed succesfully, and the second cycle students’ understanding and learning attitude increased to 91% or 21 students who passed succesfully.